Sequence analyses and evolutionary relationships among the energy‐coupling proteins enzyme I and HPr of the bacterial phosphoenolpyruvate: Sugar phosphotransferase system - Reizer, Jonathan; Hoischen, Christian; Reizer, Aiala; Pham, Tam N.; Saier, Milton H. (Protein science, 1993)
We have previously reported the overexpression, purification, and biochemical properties of the Bacillus subtilis Enzyme I of the phosphoenolpyruvate:sugar phosphotransferase system (PTS) (Reizer, J., et al., 1992, J. Biol. Chem. 267, 9158–9169). We now report the sequencing of the ptsl gene of B. subtilis encoding Enzyme I (570 amino acids and 63, 076 Da). Putative transcriptional regulatory signals are identified, and the pts operon is shown to be subject to carbon source‐dependent regulation. Multiple alignments of the B. subtilis Enzyme I with (1) six other sequenced Enzymes I of the PTS from various bacterial species, (2) phosphoenolpyruvate synthase of Escherichia coli, and (3) bacterial and plant pyruvate:phosphate dikinases (PPDKs) revealed regions of sequence similarity as well as divergence. Statistical analyses revealed that these three types of proteins comprise a homologous family, and the phylogenetic tree of the 11 sequenced protein members of this family was constructed. This tree was compared with that of the 12 sequenced HPr proteins or protein domains. Antibodies raised against the B. subtilis and E. coli Enzymes I exhibited immunological cross‐reactivity with each other as well as with PPDK of Bacteroides symbiosus, providing support for the evolutionary relationships of these proteins suggested from the sequence comparisons. Putative flexible linkers tethering the N‐terminal and the C‐terminal domains of protein members of the Enzyme I family were identified, and their potential significance with regard to Enzyme I function is discussed. The codon choice pattern of the B. subtilis and E. coli ptsI and ptsH genes was found to exhibit a bias toward optimal codons in these organisms. Quantitative analysis of this bias indicated that the ptsH genes have higher bias toward codons favored in highly expressed genes than the ptsI genes, in agreement with their relative levels of expression.